A Review of Project Management Research in Libya’s Construction Industry: A Literature Analysis - Bin Salim Mohammed Albahloul Almukhtar; Dr. Vijayan Ramasamy (Educational Administration: Theory and Practice, 2024)
The construction industry is essential to Libya’s economic growth, supporting adjacent sectors and making a substantial contribution to GDP and employment. Nevertheless, despite its economic significance, little is known about how well project management techniques work in Libya’s building sector. In order to assess the factors and approaches applied in earlier studies on project management in Libya, with an emphasis on both public and private sector projects, this study does a narrative literature review. After a thorough search of Google Scholar, eight peer-reviewed publications from 2019 to 2024 were chosen. The results show an excessive dependence on broad frameworks that are not adapted to Libya’s particular building environment and a deficiency of thorough evaluation methods. Critical topics like risk mitigation, strategy planning, and stakeholder management are also still poorly understood. In order to improve productivity and performance in Libya’s construction industry, this assessment emphasizes the critical need for context-specific research and the creation of regional project management frameworks.